“Keep That in Mind!” The Role of Positive Affect in Working Memory for Maintaining Goal-Relevant Information - Figueira, Jessica S. B.; Pacheco, Luiza B.; Lobo, Isabela; Volchan, Eliane; Pereira, Mirtes G.; de Oliveira, Leticia; David, Isabel A. (Frontiers in Psychology, 2018)
Some studies have demonstrated a beneficial role of Positive Affect on Working Memory by either applying protocols of mood induction or assessing naturally occurring state Positive Affect. However, there are no studies directly linking Positive Affect as a stable personality-like trait with Working Memory. We aimed to address this potential relationship using PANAS scale and Contra-lateral Delay Activity (CDA) as measures of trait Positive Affect and Working Memory Capacity, respectively. We also sought to investigate the impact of a neutral or unpleasant emotional state on this relationship. Participants performed a change detection task, while a neutral or an unpleasant emotional state was induced. Our results showed a positive robust correlation between trait Positive Affect and Working Memory Capacity for both the neutral and unpleasant emotional states, as revealed by the neuroelectrophysiological gold-standard measure of Working Memory, namely, CDA. These data suggests a tangible role of trait Positive Affect in the cognitive ability of maintaining goal-relevant information in Working Memory, as such that even a highly disruptive state is not sufficient to corrupt this relationship.